Sex-Specific Gene Expression and Life Span Regulation. (October 2017) - Tower, John
Abstract : Aging-related diseases show a marked sex bias. For example, women live longer than men yet have more Alzheimer's disease and osteoporosis, whereas men have more cancer and Parkinson's disease. Understanding the role of sex will be important in designing interventions and in understanding basic aging mechanisms. Aging also shows sex differences in model organisms. Dietary restriction (DR), reduced insulin/IGF1-like signaling (IIS), and reduced TOR signaling each increase life span preferentially in females in both flies and mice. Maternal transmission of mitochondria to offspring may lead to greater control over mitochondrial functions in females, including greater life span and a larger response to diet. Consistent with this idea, males show greater loss of mitochondrial gene expression with age. Trends: Sexual differentiation pathways include cell-autonomous mechanisms that continue to be required in the adult to maintain cellular sexual identity. Maternal-only transmission of mitochondrial genes and additional genetic conflicts between male and female may keep deleterious gene alleles in the population that create the aging phenotype. Gene expression changes during aging are consistent with mitochondrial maintenance failure: decreased mitochondrial gene expression, inflammation, oxidative stress response, and proteotoxicity response. Maternal-only transmission of mitochondrial genes may result in relatively greater female control over mitochondria, leading to longer life span, greater stress resistance, and greater response to diet in females. Sex-dimorphic hormones, including steroid hormones, may promote aging by regulating trade-offs between reproductive metabolism versus mitochondrial maintenance.